PROPERTY REGISTRY. CREATION AND CONTENT: PROPERTY REGISTRY. CREATION AND CONTENT - Niyazi-Yusuf, Mirem (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The property register is a data system for real estate on the territory of the Republic of Bulgaria and consists of the lots of individual properties. It contains the acts that recognize, transfer, amend or terminate the right of ownership or other real right to real estate. The foreclosures and mortgages of NI are included in the property register. The register shows the status of the specified circumstances after the last entry and makes it possible to follow chronologically the changes in the entered circumstances, as well as the entered acts. In the Property Register inquiries can be made about the ownership of the properties, the owners and the real rights and restrictions on them. Inquiries in the register can be made on-site at the registration offices in the country or via the Internet after payment of a fee specified in the price list and registration of the user.